Performance and combustion characteristics of a novel crank-rocker engine - Mohammed, S.E. (Korean Society of Mechanical Engineers, 2017)
The performance and combustion characteristics of a novel internal combustion engine, called the crank-rocker, have been investigated experimentally. The engine specifications are gasoline-port injection, four-stroke, spark-ignition, and single-curved cylinder. The ignition timing was initially set at 8.60 CA BTDC, 1800 rpm based on a small conventional engine. The equivalence ratio, lambda (λ) was varied at rich, stoichiometric, and lean conditions. The entire tests were performed at six different engine speeds of 1800, 2000, 2200, 2400, 2600 and 2800 rpm, with each one operating at wide open throttle. The performance data such as indicated torque, indicated power, indicated specific fuel consumption, and indicated thermal efficiency were calculated. The combustion characteristics such as cylinder pressure, mass fraction burned, heat release rate, P-V diagram, and indicated mean effective pressure were also determined. The results obtained from the crank-rocker engine were compared with the experimental results obtained from the conventional engine (benchmark engine). The results showed that the indicated torque, power and thermal efficiency of crank-rocker engine is higher than normal slidercrank engine. The indicated torque and power increased by about 6.28 , while the indicated specific fuel consumption is lower by 4.69 . In general, the engine has similar indicated performance characteristics to the conventional engine, but the combustion characteristics differ because the peak values of the combustion pressure and heat release occur at higher crank angle ATDC. This was found to be due to the dwelling of piston at TDC. The combustion rate and mixture of the novel crank-rocker engine burned faster, resulting in shorter combustion duration and ignition delay period than the conventional slider-crank engine. © 2017, The Korean Society of Mechanical Engineers and Springer-Verlag GmbH Germany.